Legal Consequences of Unregistered Fiduciary Guarantee Deed - Markus Gunawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Discussion regarding legal arrangements for fiduciary guarantee deeds that are not registered for research studies at FIFGROUP Batam Branch is regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees, which is regulated regarding fiduciary guarantees contained in Article 1 paragraph (1) and (2) and what are the procedures for implementing the fiduciary guarantee in Article 11. The obstacle to the fiduciary guarantee deed not being registered is the need to complete documents such as identity cards, family cards (KK), and the applicant's address. From the results of this study, it was concluded that the legal arrangements are contained in Law Number 42 of 1999 concerning Fiduciary Guarantees. As well as the factor that becomes the obstacle is the incompleteness of the documents. So that the government conducts socialization related to the fiduciary registration process considering that the legal regulations already exist, finance companies must pay attention to drawing up a fiduciary guarantee deed and register it through a notary.